Producción de soya (Glycine max L.) bajo tres sistemas de labranza - Rojas Palacio Hernán; González V. William; Terreros O. Gilberto (Acta Agronómica)
The goals of this consisted in economically analyzing the conventional pattern with regard to minimum tillage and non tillage; evaluating the influence of the tillage systems on the physical properties of the soil and on the soybean's growth and yield. The experiment was stablished on clay soil. The experimental design employed was that of hierarchy-arranged random blocks with three repetitions (9 experimental units). The conventional tillage permitts the improvement of the physical conditions of the soil, performs a better control on the weeds, gives the soybean plant a full growth and yield causing the highest profitability. The second treatment showing the best efficiency was the minimum tillage. Se evaluó la influencia de los sistemas de labranza convencional, mínima y no labranza sobre las propiedades físicas del suelo, en el desarrollo y producción de la soya. El experimento se estableció en suelo arcilloso. El diseño experimental fue el de bloques al azar jerarquizados con tres repeticiones (9 unidades experimentales). La labranza convencional mejora las condiciones físicas del suelo, ejerce mayor control sobre las malezas, confiere a la planta de soya apropiado desarrollo y producción ocasionando así la mayor rentabilidad. El segundo tratamiento en eficiencia fue el de la labranza mínima.